Human, nature, and architecture - Johannes Widodo (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
Human is the centre of natural exploitation and built environment, a belief that has been existed since the beginning of civilization when human started to adapt into the natural environment and to articulate nature into built-environment. Human as creator and innovator of the built environment put himself at the centre of the universe: geographically is at the middle ground in between the mountain and the waterfront, chronologically is in between the sunrise and the sunset, and ideologically is in between heaven above and underworld beneath the earth. He stands at the middle of circles that define inside and outside and denote sacred and profane. Water is the essence of life. Therefore, the forested hills and mountains that provide steady supply of fresh water are preserved and well protected, spiritually and physically. To ensure the continuous flow of the lifeline, the forests are protected against violations and destructions, through rituals and social rules. The choice of location for the built-up area of the settlement is carefully considered against natural and supra-natural factors, in order to ensure the harmonious relationships between human, nature, and the spirits. In rational sense, it is to ensure the survivability of the community’s existence and its livelihood. © 2019 Johannes Widodo